A Lutheran Reflection on The One Mediator, The Saints, and Mary in Relation to the Question: How Do Lutherans Understand Prayer for Other People? - Persaud, Winston D. (Dialog, 2013)
In this article, the author offers a critical, appreciative appraisal of The One Mediator, The Saints, and Mary (1992), which was the publication that emerged from the eighth round of the U.S. Lutheran-Catholic Dialogue. Writing from a Lutheran perspective and using the Joint Declaration on the Doctrine of Justification (JDDJ, October 31, 1999) as a critical hermeneutical lens, the author points to Luther's theological conviction concerning how Mary—the mother of the Lord Jesus Christ—and departed saints are to be regarded. Luther's emphasis on Christ the only Mediator was highlighted. Reflection on this text was done in light of the theme of the dialogue's eleventh round, “The Hope of Eternal Life.” Prayer is always in and through Jesus Christ.